2019
DOI: 10.1111/jnu.12469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Online Training Program in Smoking Cessation Interventions in Hospitals

Abstract: Purpose To assess changes in the self‐reported performance of smoking cessation interventions according to the 5A's model (Ask; Advise; Assess; Assist; and Arrange follow‐up) among clinicians; and to identify the main barriers and facilitators in smoking cessation implementation before and after an online smoking cessation training program. Design Pre‐post evaluation. Methods We assessed self‐reported smoking cessation interventions in the implementation of the 5A's model among clinicians working in Catalan ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
3
15
1
Order By: Relevance
“…Tobacco cessation training initiatives can help address these challenges and improve the practices of healthcare professionals. Brief tobacco cessation training programs for health professionals have been associated with an increase in the delivery of the 5As for tobacco cessation (Martínez et al., 2018, 2019; Payne et al., 2014) increasing participants' perceived self‐efficacy (Payne et al., 2014) and their positive opinions and attitudes towards such a role (Martínez et al., 2018; Payne et al., 2014). The structure of such tobacco cessation training programs varies, however, the content is generally based on three topics: the basic science (the principles on tobacco use and associated diseases); the clinical science (the behavioral strategies, such as the use of the 5As, and pharmacological agents); and the socio‐political topics of tobacco control (to encourage greater advocacy and lobbying), which tends to be inadequately covered (Ye et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco cessation training initiatives can help address these challenges and improve the practices of healthcare professionals. Brief tobacco cessation training programs for health professionals have been associated with an increase in the delivery of the 5As for tobacco cessation (Martínez et al., 2018, 2019; Payne et al., 2014) increasing participants' perceived self‐efficacy (Payne et al., 2014) and their positive opinions and attitudes towards such a role (Martínez et al., 2018; Payne et al., 2014). The structure of such tobacco cessation training programs varies, however, the content is generally based on three topics: the basic science (the principles on tobacco use and associated diseases); the clinical science (the behavioral strategies, such as the use of the 5As, and pharmacological agents); and the socio‐political topics of tobacco control (to encourage greater advocacy and lobbying), which tends to be inadequately covered (Ye et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We found that a high proportion of healthcare professionals completed the four modules of the e-learning program. However, the completion of all the modules and the exam was lower than expected in comparison to health professionals who did the same e-learning smoking cessation program in Catalonia (Spain) (Martínez et al, 2019). Doctors and participants from Bolivia had higher rates of completion, including the modules and taking the test, compared to the other two countries.…”
Section: Discussionmentioning
confidence: 72%
“…Our study explored several of these factors, but did not study training. However, a previous study conducted in Catalonia showed that training health professionals increases the level of performance of the 5As [19]. In this sense, future research should continue exploring these factors at multiple levels, including the ones we have explored in this study that characterize patients (such as age, gender and comorbidities) and hospitals (such as unit of admission and provision of smoking cessation services).…”
Section: Discussionmentioning
confidence: 91%
“…In order to monitor adherence to tobacco cessation guidelines, several studies have relied upon provider self‐reports [16,17]. Studies conducted among health‐care providers show a good implementation of the first two components of the 5As model, ask and advise, ranging from 60 to 75%, but lower implementation for the remaining following components [18–21]. Further, studies comparing the performance of providers with patients’ perception show that providers tend to overestimate their performance [22,23].…”
Section: Introductionmentioning
confidence: 99%